Producción de bloques de tierra comprimida BTC como alternativa en la construcción de vivienda rural sustentable en ell minicipio de Dosquebradas, Risaralda - Sabogal Vargas, Carol Vanessa
. In this article, the  production of compressed earth blocks composed of a mixture of volcanic ash, silt and clay, was proposed as an alternative for the construction of non-structural walls in sustainable rural housing in the municipality of Dosquebradas. The blocks produced allowed us to verify and obtain good mechanical resistance to compression, compared to conventional bricks, generating a sustainable construction alternative once the raw material was obtained from soil left over from excavation.